Whey Protein as an Adjuvant Therapy for Wound Healing and Infection Control: A Systematic Review and Meta-Analysis of Clinical and Preclinical Evidence - Aliva Nabila Farinisa; Niken Puruhita; Yan Wisnu Prajoko; Felix Setiawan (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Impaired wound healing and subsequent infections represent a significant clinical and economic burden. Nutritional status, particularly high-quality protein provision, is a critical, modifiable determinant of healing outcomes. Whey protein (WP), a rich source of essential amino acids and unique bioactive components, has emerged as a promising adjuvant therapy. Methods: We conducted a systematic review and meta-analysis adhering to PRISMA guidelines. We searched PubMed, Scopus, and Web of Science from January 2015 to December 2024 for clinical randomized controlled trials (RCTs) and preclinical controlled studies evaluating WP supplementation on wound healing and infection. Rigorous inclusion criteria led to the selection of seven studies (four clinical RCTs, three preclinical) for quantitative synthesis. Data were pooled using a random-effects model to calculate Standardized Mean Differences (SMD) for continuous outcomes and Odds Ratios (OR) for dichotomous outcomes. Results: The meta-analysis of four clinical RCTs (n=340 patients) demonstrated that WP supplementation significantly accelerated wound healing (SMD = 0.78; 95% CI 0.45, 1.11; p < 0.0001) with moderate heterogeneity (I²=38%). Furthermore, WP significantly reduced the odds of wound infection by 48% (OR = 0.52; 95% CI 0.31, 0.87; p=0.01) with no heterogeneity (I²=0%). Preclinical synthesis (3 studies, n=62 animals) revealed a significant reduction in pro-inflammatory cytokines (TNF-α, IL-6) at the wound site (SMD = -1.15; 95% CI -1.67, -0.63; p < 0.0001). Conclusion: This meta-analysis provides robust quantitative evidence that whey protein functions as an effective adjuvant therapy, significantly enhancing wound repair and providing clinically relevant infection control. These benefits appear to be mediated by a dual mechanism: providing essential anabolic substrates for tissue repair and exerting potent immunomodulatory and antioxidant effects via bioactive components like lactoferrin and cysteine.